Melatonin Attenuates Dasatinib-Aggravated Hypoxic Pulmonary Hypertension via Inhibiting Pulmonary Vascular Remodeling - Rui Wang; Rui Wang; Jinjin Pan; Jinzhen Han; Miaomiao Gong; Liang Liu; Yunlong Zhang; Ying Liu; Dingyou Wang; Qing Tang; Na Wu; Lin Wang; et al. (Frontiers in Cardiovascular Medicine, 2022)
Dasatinib treatment is approved as first-line therapy for chronic myeloid leukemia. However, pulmonary hypertension (PH) is a highly morbid and often fatal side-effect of dasatinib, characterized by progressive pulmonary vascular remodeling. Melatonin exerts strong antioxidant capacity against the progression of cardiovascular system diseases. The present work aimed to investigate the effect of melatonin on dasatinib-aggravated hypoxic PH and explore its possible mechanisms. Dasatinib-aggravated rat experimental model of hypoxic PH was established by utilizing dasatinib under hypoxia. The results indicated that melatonin could attenuate dasatinib-aggravated pulmonary pressure and vascular remodeling in rats under hypoxia. Additionally, melatonin attenuated the activity of XO, the content of MDA, the expression of NOX4, and elevated the activity of CAT, GPx, and SOD, the expression of SOD2, which were caused by dasatinib under hypoxia. In vitro, dasatinib led to decreased LDH activity and production of NO in human pulmonary microvascular endothelial cells (HPMECs), moreover increased generation of ROS, and expression of NOX4 both in HPMECs and primary rat pulmonary arterial smooth muscle cells (PASMCs) under hypoxia. Dasatinib up-regulated the expression of cleaved caspase-3 and the ratio of apoptotic cells in HPMECs, and also elevated the percentage of S phase and the expression of Cyclin D1 in primary PASMCs under hypoxia. Melatonin ameliorated dasatinib-aggravated oxidative damage and apoptosis in HPMECs, meanwhile reduced oxidative stress level, proliferation, and repressed the stability of HIF1-α protein in PASMCs under hypoxia. In conclusion, melatonin significantly attenuates dasatinib-aggravated hypoxic PH by inhibiting pulmonary vascular remodeling in rats. The possible mechanisms involved protecting endothelial cells and inhibiting abnormal proliferation of smooth muscle cells. Our findings may suggest that melatonin has potential clinical value as a therapeutic approach to alleviate dasatinib-aggravated hypoxic PH.